Spinel ZnMn2O4 Nanocrystal‐Anchored 3D Hierarchical Carbon Aerogel Hybrids as Anode Materials for Lithium Ion Batteries. (2nd April 2014) - Yin, Longwei; Zhang, Zhiwei; Li, Zhaoqiang; Hao, Fengbin; Li, Qun; Wang, Chengxiang; Fan, Runhua; Qi, Yongxin
Abstract : To improve the electrochemical performance of spinel ZnMn2 O4, i.e., its limited specific capacity, cycling performance, and rate properties, owing to its inherent poor electrical conductivity and large volume changes during lithiation and delithiation processes, spinel ZnMn2 O4 nanocrystals are anchored into a three dimensional (3D) porous carbon aerogel (CA) through a facile solution immersion chemical route. The designed 3D spinel ZnMn2 O4 /CA hybrids display the advantages of both spinel ZnMn2 O4 and porous CA: enormous interfacial surface area, connected 3D framework, abundant porosity and high electron transport properties of CA, and electrochemical properties of nanostructured spinel ZnMn2 O4 oxide materials. The synthesized novel ZnMn2 O4 /CA hybrids display a significantly improved electrochemical performance, with a high reversible specific capacity, and high‐rate capability, as well as an excellent cycling performance, superior to that of previously reported ZnMn2 O4 ‐based materials. After 50 cycles, the 50%ZnMn2 O4 /CA hybrid displays a reversible capacity of 833 mAh g −1 at a current density of 100 mAg ‐1, much higher than the theoretical capacity of 784 mAh g −1 for pure spinel ZnMn2 O4 materials, corresponding to a Coulombic efficiency of 99.9%. The greatly improved cycle stability, specific capacity, and high rate performance of the ZnMn2 O4 /CA hybrids can be attributed to the synergistic interaction between spinel‐structured ZnMn2 O4 nanoparticles and the 3D interconnected porous CA matrix. Abstract : Based on the advantages of high surface area, abundant porosity, the good electron transport properties of carbon aerogel (CA) materials, and the good electrochemical properties of nanostructured spinel ZnMn2 O4 oxide materials, these 3D interconnected spinel ZnMn2 O4 /CA hybrids display a significantly improved electrochemical performance with a high reversible specific capacity, specific capacity, and rate capability, as well as excellent cycling performance.